2020
DOI: 10.1130/b35233.1
|View full text |Cite
|
Sign up to set email alerts
|

Channel narrowing by inset floodplain formation of the lower Green River in the Canyonlands region, Utah

Abstract: The lower Green River episodically narrowed between the mid-1930s and present day through deposition of new floodplains within a wider channel that had been established and/or maintained during the early twentieth century pluvial period. Comparison of air photos spanning a 74-yr period (1940−2014) and covering a 61 km study area shows that the channel narrowed by 12% from 138 ± 3.4 m to 122 ± 2.1 m. Stratigraphic and sedimentologic analysis and tree ring dating of a floodplain trench corroborates the air photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 44 publications
4
43
0
Order By: Relevance
“…In the Green River, Allred and Schmidt (1999) showed that channel narrowing by ~17 m occurred at the upper end of our study area between 1962 and 1985 by vertical aggradation of ~1.1 m of sediment on top of bars within the active channel; aggradation occurred in 12 of the years in this period. Walker et al (2020) showed that the Green River within and below the study area narrowed by ~12 m between the mid‐1980s and 2014 by the vertical aggradation of ~1.5 m of sediment also on top of active channel bars. These numbers indicate that ~1.5 and ~2 million metric tons of sand accumulated along the ~110‐km river segment in our study area (GR‐GR to GR‐MB) between 1962 and 1985 and the mid‐1980s and 2014, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Green River, Allred and Schmidt (1999) showed that channel narrowing by ~17 m occurred at the upper end of our study area between 1962 and 1985 by vertical aggradation of ~1.1 m of sediment on top of bars within the active channel; aggradation occurred in 12 of the years in this period. Walker et al (2020) showed that the Green River within and below the study area narrowed by ~12 m between the mid‐1980s and 2014 by the vertical aggradation of ~1.5 m of sediment also on top of active channel bars. These numbers indicate that ~1.5 and ~2 million metric tons of sand accumulated along the ~110‐km river segment in our study area (GR‐GR to GR‐MB) between 1962 and 1985 and the mid‐1980s and 2014, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These quantities are equivalent to ~3% and ~4% of the average annual sand load over these respectively time periods or ~1% of the sand load prior to 1959. Thus, channel margin and floodplain deposition of only a small amount of the annual load is required to achieve the observed channel narrowing (Walker et al, 2020). This is consistent with the findings of Grams and Schmidt (2005) that floodplain accretion in Dinosaur National Monument was ~1% of the annual sand load.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6; Table 2). Several of these are functionally-related, such as: Agricultural/ urban areas as major drivers of water usage (USE); flow regulation/ flood dampening (DOR) as controlling sediment supply (SED) as well as channel width and morphology (Grams et al 2020, Walker et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…channel adjustment may result principally from changes in the frequency and intensity of sediment transport 192 and therefore be amenable to a mechanics based solution, other factors may also contribute. For example, interannual vegetation growth -along channel banks, on bars, and within the upstream catchment -could contribute significantly both in changing the entrainment threshold, and also by potentially introducing lags and hysteresis in channel response 193,194 .…”
Section: /36mentioning
confidence: 99%